2001
DOI: 10.1590/s0104-11692001000500013
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Bibliográfico De Publicações Sobre a Atividade Administrativa Da Enfermagem Em Saúde Mental

Abstract: Aiming at studying the mental health nurse's management activity as an instrument in the work process, a bibliographic study on nursing publications from 1988 to 1997 which concerned that topic was carried out. By reading and critically analyzing 8 articles and 19 selected theses and dissertations, the major characteristics of such practice were identified, namely: mental health nurses are responsible for the nursing team and care according to the logic determined by the institution; their actions are not plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
18

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 8 publications
(20 reference statements)
0
2
0
18
Order By: Relevance
“…Também, que os enfermeiros se ocupam, muitas vezes de forma prioritária, com atividades que têm por finalidade a organização do trabalho dos demais profissionais (6) .…”
Section: )unclassified
See 2 more Smart Citations
“…Também, que os enfermeiros se ocupam, muitas vezes de forma prioritária, com atividades que têm por finalidade a organização do trabalho dos demais profissionais (6) .…”
Section: )unclassified
“…Embora o papel do enfermeiro em saúde mental seja o de agente terapêutico, cujo objetivo fundamental é auxiliar o paciente a aceitar a si próprio e a melhorar as suas relações pessoais (6) , na prática centra-se, principalmente, no desenvolvimento de atividades burocrático-administrativas, com escassa ou nenhuma atuação técnico-assistencial específica (3) .…”
Section: )unclassified
See 1 more Smart Citation
“…A bibliographic study on nursing management activity in mental health showed that nurses are the professionals that least perform direct care to the population, and most of their time is taken by organizational activities in the institutions they work for (10) . The literature (11) points out that the difficulty in positioning nurses in multidisciplinary teams is justified because the team does not have a sole working goal and each professional works with a different theoretical reference, hindering a full view of patients who are approached in a fragmented manner.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse estudo, concluiu-se que os trabalhos realizados em instituições extra-hospitalares mostraram uma tendência de mudança nas práticas desses profissionais, os quais vêm desenvolvendo atividades terapêuticas e grupais, apresentando um espaço mais definido enquanto profissional e reconhecido na equipe de saúde mental (17) .…”
Section: A Enfermagem Psiquiátrica E O Cuidarunclassified